2023
DOI: 10.1038/s41559-023-01999-w
|View full text |Cite
|
Sign up to set email alerts
|

Peer review perpetuates barriers for historically excluded groups

Abstract: w reviewer homophily. These analyses leverage data from 31 studies, which cumulatively examined 312,740 manuscripts submitted to >640 journals-including Nature Portfolio journals, Science and Proceedings of the National Academy of Sciences. Our dataset represents 4,529,971 author position/demographic/review stage interactions, which upon publication will be the largest publicly available dataset of this kind for future work to build upon. Finally, we describe the current landscape of peer review in the subfiel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
25
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 45 publications
(73 reference statements)
1
25
0
Order By: Relevance
“…Peer review has also been reported as a barrier for historically excluded groups, including women. When peer review data was recently analyzed from 312,740 manuscripts in biological sciences, they reported that female authors had worse or similar outcomes at each step of the review than male authors …”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Peer review has also been reported as a barrier for historically excluded groups, including women. When peer review data was recently analyzed from 312,740 manuscripts in biological sciences, they reported that female authors had worse or similar outcomes at each step of the review than male authors …”
Section: Resultsmentioning
confidence: 99%
“…Our data indicates that the representation of females in academia and as mentors for female trainees can improve authorship outcomes; however, our noted discrepancy around gender differences and authorship is often amplified in other underrepresented groups. For instance, it is well observed that differences related to author ethnicity and affiliation affect representation across publications . One way to mitigate this for gender, ethnicity, and LGBTQ+ status is to create a greater sense of inclusion .…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Providing journal data and conducting these types of analyses will allow editorial boards and journal readers to understand how, where, and in what ways underrepresentation occurs and is affecting progress toward equity in scientific publishing. Of note, there are other strategies to enhance representation in the peer review process that are worthy of conversation and consideration (see Smith et al, 2023, for a review of such considerations), including fully unblinded reviews or, alternatively, double- or triple-blinded reviews (Tóth, 2020), and requiring positionality statements in all publications (Jafar, 2018).…”
mentioning
confidence: 99%